Criminalization of Social Protest: Future research - Carolijn Terwindt (Oñati Socio-Legal Series)
This Special Issue of the Oñati Socio-Legal Series is dedicated to an exploration of particular features of and analytical approaches to the criminalization of social protest about natural resources. This epiloguehighlights four areas for future research: (1) the definition and use of the term ‘criminalization of social protest’and the development of an analytical apparatus; (2) patterns, typologies, and legal strategies of criminalization; (3) the embeddednessof processes of criminalization in the broader political decision-making procedures about natural resources;(4) counter-strategies. In the description of these areas, the author draws on the papers in this Special Issue and the collective reflection during the Workshop in 2012.